H Hubungan Dukungan Sosial Keluarga Dengan Efikasi Diri Remaja Di SMAN 1 Banjarmasin - Mariatul; Dhian Ririn Lestari; Eka Santi (LPPM Universitas Sari Mulia, 2024)
Background: Adolescence is a transitional period from childhood to adulthood. During adolescence, changes occur involving three aspects: biological, cognitive, and socio-emotional. Adolescence is referred to as a period of